Manajemen Komunikasi Stigma pada Perempuan Lajang - Frelians, Pricilla Pascadeany; Astuti, RA Vita (Jurnal ILMU KOMUNIKASI, 2024)
The patriarchal and collective culture necessitates women to marry at a certain age, or else they face various stigmas. Women need strategies to deal with these stigmas. This study aims to uncover the Stigma Management Communication (SMC) among single adult women, including their backgrounds and strategies in dealing with stigma. This research is qualitative research with multiple-case study method. Data was collected through interviews with women over 25 years old who currently have a job. Based on Meisenbach's concept of SMC, the results show that SMC is performed differently, such as ignoring, accepting, or confirming according to their individual situations.